Substantiation of trip duration mathematical model at international trucking - Бондарєв, Сергій Іванович (Eastern-European Journal of Enterprise Technologies, 2013)
The coordination of transportation with stock facilities requires the development of accurate schedules of traffic and the definition of the exact time of turnaround trip. The development of these schedules is a laborious work for managers. Therefore, in order to facilitate and automate the time-consuming development of schedules of traffic we have proposed a mathematical model for definition of the time of transportation at international trucking. The article presents materials of theoretical analysis and the algorithm of the mathematical model to determine the duration of turnaround trip at international trucking, taking into account the time for moving, breaks and rest according to the rules of European Agreement concerning the Work of Crews of Vehicles Engaged in International Road Transport (AETR). An algorithm was developed to calculate the optimal duration of a trip in order to coordinate the transportation and loading equipment, as well as for the development of schedules of traffic while organizing international trucking in accordance with the AETR. Also the materials of calculations of the duration of trucking for turnaround trips according to experimental data were presented, using the proposed mathematical model and the effect of individual parameters on the total time of trucking.